Analisis Prestasi Belajar Matematika Ditinjau dari Kemampuan Berpikir Kritik dan Konsep Diri Siswa - Dona Katarina (Universitas Indraprasta PGRI Jakarta, 2017)
This study aims to determine how much influence mathematics learning achievement can be increased in terms of students' critical thinking and self-concept. The subjects of the study were Junior High School Students 34 23 and 42 in Pademangan, North Jakarta. The number of samples of 90 people with each sample of each school as many as 30 people. Data analysis using descriptive statistics method and test technique requirement of data analysis. The results showed (1). there is a significant direct influence of the ability of critical thinking and self-concept to the achievement of learning mathematics Students where the magnitude of the influence of the ability to think criticism of learning achievement are, (2). There is a significant influence of self-concept on learning achievement where the influence of self concept to learning achievement, (3). The direct influence of critical thinking ability on student self concept where the influence of critical thinking ability to self concept. (1). The better the students' critical thinking skills the higher the learning achievement achieved in the mathematics lesson. (2). The better the student's self concept in the math lesson the better the achievement. (3). A good environment, educated teachers and parents who can make children more confident and able to think critically is a form of motivation that aims to improve mathematics learning achievement.